(untitled) (Research, Society and Development, 2024)
Introduction: Imperforate hymen is a rare congenital anomaly that obstructs normal menstrual flow, leading to the accumulation of blood in the uterus (hematometra) and vagina (hematocolpos). This condition can result in severe complications such as intense pelvic pain, abdominal distension, and urinary retention. Objective: To report the case of an adolescent patient with an imperforate hymen, highlighting the importance of early diagnosis and the use of a non-traditional surgical technique. Methods: Data collection was performed through the review of the patient’s medical records and imaging exams. Results: A 14-year-old female patient presented with symptoms of cyclic pelvic pain, abdominal distension, and urinary retention. The diagnosis was confirmed by ultrasound and magnetic resonance imaging, revealing hematometra and hematocolpos. The patient underwent hymenectomy, utilizing high-frequency surgery for the resection of the hymenal membrane at its base. This technique generally eliminates the need for stitches as cauterization seals the blood vessels. However, due to the presence of a raw area, it was necessary to suture the base of the hymenal ring with simple stitches. The surgery was successful, resulting in the drainage of blood, with recovery without complications. Conclusion: Early diagnosis and appropriate treatment of imperforate hymen are essential to prevent severe complications and improve the quality of life of patients. Continuous awareness and education of healthcare professionals about this condition are fundamental to ensure that rare congenital anomalies are promptly recognized and treated.